Comunicação, educação e história : a recepção do discurso do Memorial da Resistência de São Paulo por parte de professores (as) e aluno (as) do Ensino Fundamental II e Ensino Médio - Mello, Felipe Carvalho Corrêa de (2017)
The "Memorial da Resistência de São Paulo" preserves and comunicate the memories e narratives about the resistance, the control and repression along the History of republican Brazil, privileging the narratives anda memories of Vargas Era (1930-1945) e and the civilian-military ditatorship (1964-1985). In our research, in a first step, we seek to delineate the communicative dimensions of the "Memorial da Resistência de São Paulo". This process involves the theoretical argument that this museological institution is constituted as a means of communication / media, being part of the field of Communication. In a second step, considering that the formal school is still the privileged space for reflection on social reality, we conducted a research to understand the process of reception of the speech of the "Memorial da Resistência de São Paulo" by teachers and students of the Elementary School and High School. In this context, we seek to illuminate the process of (re) production of hegemonic and / or counter-hegemonic meanings about the civilian-military dictatorship. Based on the reflections presented by the fields of Communication, History and Education, we conceive, on the one hand, that the discourse of the "Memorial da Resistência de São Paulo" is constituted as a discourse predisposed to operate as a clash with the hegemonic conception about the dictatorship movement in the media and the school field. On the other, we understand as hegemonic meanings the set of discourses that relativize and / or silence about violence; torture; the corruption; violations of human rights; censorship; the genocide of indigenous peoples; the struggles of resistance, etc. occurred during the civilian-military dictatorship, to the point of justifying and legitimizing it and, in some everyday contexts, to claim for its return. This research is situated at the confluence of four theoretical fields: (1) Latin American Reception Studies; (2) British Cultural Studies; (3) Mediation Theory and (4) French Line Discourse Analysis. These four fields are tied by the reflections of the field of Communication / Education.